2006
DOI: 10.1086/504809
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid and Serotonergic Drug Interactions: A Retrospective Survey

Abstract: On the basis of our experience, we suggest that, if the clinical situation warrants use of linezolid in a patient receiving an SSRI, linezolid may be used concomitantly with SSRIs, without a 14-day washout period and with careful monitoring for signs and symptoms of serotonin syndrome. Serotonergic agents should be promptly discontinued if serotonin syndrome is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 14 publications
1
56
0
3
Order By: Relevance
“…A retrospective review of 20 comparator-controlled linezolid clinical trials involving Ͼ10,000 participants identified approximately 2.8-fold higher, but not significantly different, incidence of serotonin toxicity for linezolid-treated versus comparator-treated patients (40). A number of drugs with potential (alone or in combination) for linezolid interaction leading to serotonin syndrome, including certain tricyclic antidepressants, serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, and opioids, have been identified (13,(41)(42)(43).…”
Section: Figmentioning
confidence: 99%
“…A retrospective review of 20 comparator-controlled linezolid clinical trials involving Ͼ10,000 participants identified approximately 2.8-fold higher, but not significantly different, incidence of serotonin toxicity for linezolid-treated versus comparator-treated patients (40). A number of drugs with potential (alone or in combination) for linezolid interaction leading to serotonin syndrome, including certain tricyclic antidepressants, serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, and opioids, have been identified (13,(41)(42)(43).…”
Section: Figmentioning
confidence: 99%
“…44 Medications with monoamine oxidase inhibitor activity such as linezolid may precipitate the syndrome when administered concurrently with a serotonergic agent. 45 Diagnosis requires recognition of symptoms that include mental status changes, autonomic instability (hyperthermia, heart rate and BP fluctuation, arrhythmias and diaphoresis), and neuromuscular abnormalities such as tremor, myoclonus, or hypertonicity. Symptoms of SS are usually noted to improve within 24 h after withdrawal of the offending agent(s).…”
Section: Antidepressantsmentioning
confidence: 99%
“…3 It has been noted that Boyer's criteria are more specific for serotonin toxicity than are Sternbach's criteria. 4 …”
Section: What Is the Serotonin Syndrome And How Is It Diagnosed?mentioning
confidence: 99%
“…7 Since linezolid was approved by the FDA for use, there have been 17 published case reports documenting the occurrence of symptoms of serotonin toxicity in patients receiving linezolid and SSRIs. Taylor and colleagues, 4 in a retrospective chart review of cases at the Mayo Clinic (Rochester, Minnesota), found an incidence of serotonin toxicity of 3% in patients taking SSRIs and linezolid. Table 4 lists the case reports found in the literature.…”
Section: What Is the Prevalence Of Linezolid-induced Serotonin Toxicity?mentioning
confidence: 99%